ДЕГРАДАЦИОННЫЕ ПРОЦЕССЫ ПОСЛЕ СВЧ ОТЖИГА В ДИОДНЫХ СТРУКТУРАХ С БАРЬЕРОМ ШОТТКИ Au–TiBx–SiC 6H - Исмаилов, К.; Косбергенов, Е.; Жалелов, М. (SCIENCE and SOCIETY, 2019)
The article shows the degradation processes after microwave annealing in diode structures.
Keywords: diode structure; degradation; microwave radiation